Analysis of cable insulation condition using dielectric spectroscopy and polarization/depolarization current techniques - Ariffin A.M.; Sulaiman S.; Yahya A.Z.C.; Ghani A.B.A. (2023)
Insulation of an underground cable that has been in service for a very long time is subjected to various degrees of degradation. The degradation can lead to premature breakdown of its insulation, and the cost of replacing the cable can be very expensive. Thus there is a constant need from power utility companies' point of view to continuously monitor the condition of cable insulation in order to ensure its service reliability. Among typical non-destructive tests to assess cable insulation condition are the frequency domain dielectric spectroscopy (FDDS) and polarization/depolarization current (PDC) measurements. This paper attempts to discuss the two aforementioned techniques in determining the insulation condition of several polymeric-insulated underground cables subjected to different water-based degradations. It was found that the degradation severity correlates strongly with the type of solution introduced within the cable insulation. In addition, the work performed also allows a comparison to be made between the two measurement techniques based on the insulation conditions. 2012 IEEE.